“This is ours…why should [we] be exempt?”:Black South African lesbian couples’experiences of identity in the lobola practice - Mkhize, Linda (My University, 2019)
Majority of countries in Africa consider homosexuality, or any kind of same-sex relation, illegal and immoral. The basis of this problematic notion is that ‘homosexuality is unAfrican’. South Africa remains the only country in sub-Saharan Africa where same-sex marriage has been legalized. The Civil Union Act 17 of 2006 gave same-sex couples the opportunity to get married and gain legal recognition before the law. However, the option for a customary marriage for Black same-sex couples remains unavailable. This then raises questions about the complexities of ‘African’ identities/cultures/practices alongside same-sex sexuality - what happens when one person occupies both of these seemingly contradictory identities? The aim of this study was to investigate the possibilities of disruption of the lobola practice when Black African same-sex couples decide to go through the process. Lobola, otherwise known as bride wealth or bride price, is a lengthy cultural custom that includes a prospective groom/husband sending cash/cattle or other gifts to his prospective bride/wife’s family in consideration of a customary marriage. This exploration was undertaken by looking at how individuals/couples construct, negotiate and renegotiate their identities as ‘African’ as well as ‘lesbian’ and how this all happens in the context of the lobola practice. The study further aimed to investigate how individuals/couples spoke about their identities as ‘African’ and ‘lesbian’ in the face of the anti-homosexuality discourse present in African cultures, politics and so forth. The criteria set for participation required that the participants identify as African (under the racial category of Black), queer (a gender and/or sexual identity that is non-normative), and currently undergoing or have undergone lobola negotiations. Data was collected by means of 8 individual interviews and 4 couple interviews using open-ended questions. A thematic and conversation analyses were used to interpret the data. The study allowed for engagement with existing literature on the construction African identities and negotiating this alongside queer identity in a predominantly heteronormative and gendered practice such as lobola and then built on this. The study ultimately finds that Black African queer individuals and couples both challenge and adapt to existing constructs of African identities, cultures and customs.
Submitted in fulfilment of the requirements for the degree of Master of Arts in Psychology byResearch (Dissertation), in the School of Human and Community Development, Universityof the Witwatersrand, Johannesburg, South Africa.
Keywords: Lesbian couples--South Africa; Lesbian couples--Family relationships--South Africa